Pengaruh Merokok terhadap Keefektivitasan Terapi Hipertensi pada Penderita Hipertensi Perokok Di Empat Puskesmas Tahun 2017 - Dna Raras Mardena; Anjar Mahardian Kusuma (Journal of Tropical Pharmacy and Chemistry, 2017)
Hypertension is a chronic condition of the mesh where blood pressure rises above normalized blood pressure. This study aims to measure the effect of smoking on the effectiveness of hypertension therapy in patients with hypertension of smokers at Puskesmas I Sumbang, Puskesmas II Kembaran, Puskesmas Purwokerto Timur I, Puskesmas Purwokerto Selatan 2017. Type of study used prospective cohort, in terms of patient's blood pressure with drug consumption Single 1st, 10th day, 30th day to assess effectiveness. Data were analyzed univariat and bivariate through Chi-square test. The result showed that p> 0,05 that p = 0,361 showed that there was no significant difference in the effectiveness of hypertension therapy between group of non smoker hypertension and smoker hypertension. Does not affect the effectiveness of therapy statistically. Keywords: Hypertension, Effectiveness, Amlodipine, Smoking